Hepatoprotective effects of baicalein against CCl(4)-induced acute liver injury in mice - Huang, Hai-Li (Baishideng Publishing Group Co., Limited, 2012)
AIM: To investigate the hepatoprotective effect of baicalein against carbon tetrachloride (CCl(4))-induced liver damage in mice. METHODS: Mice were orally administered with baicalein after CCl(4) injection, and therapeutic baicalein was given twice a day for 4 d. The anti-inflammation effects of baicalein were assessed directly by hepatic histology and serum alanine aminotranferease and aspartate aminotransferase measurement. Proliferating cell nuclear antigen was used to evaluate the effect of baicalein in promoting hepatocyte proliferation. Serum interleukin (IL)-6, IL-1β and tumor necrosis factor-α (TNF-α) levels were measured by enzyme-linked immunosorbent assay and liver IL-6, TNF-α, transforming growth factor-α (TGF-α), hepatocyte growth factor (HGF) and epidermal growth factor (EGF) genes expression were determined by quantitative real-time polymerase chain reaction. RESULTS: CCl(4)-induced acute liver failure model offers a survival benefit in baicalein-treated mice. The data indicated that the mRNA levels of IL-6 and TNF-α significantly increased within 12 h after CCl(4) treatment in baicalein administration groups, but at 24, 48 and 72 h, the expression of IL-6 and TNF-α was kept at lower levels compared with the control. The expression of TGF-α, HGF and EGF was enhanced dramatically in baicalein administration group at 12, 24, 48 and 72 h. Furthermore, we found that baicalein significantly elevated the serum level of TNF-α and IL-6 at the early phase, which indicated that baicalein could facilitate the initiating events in liver regeneration. CONCLUSION: Baicalein may be a therapeutic candidate for acute liver injury. Baicalein accelerates liver regeneration by regulating TNF-α and IL-6 mediated pathways.